تباين عقاب السرقة في الفقه الإسلامي عن القانون الجزائي العراقي - مهدي اركان عبيد (lark, 2019)
Summary of the research Theft is a crime many religious texts prohibit it and define its punishment precisely where no one is able to decrease, increase or replace it. Thus, jurists define Alhaad (limits set by Allah) as a punishment ordained by Allah. In fact, what a thief asks for is only the money, while killing or raping is a subordinate—it is not an end. As a result, cutting the hand is to put an end for this materialistic motive once and for all. This punishment gives rise to affect thief’s financial gain and in this way Sharia has counteracted this psychological factor, theft, by another one. According to worldly law theft, for money only, is a misdemeanor that could be punished by prison. One of the simplest differences between Sharia and law is that the former is revealed by Allah, the All-Knowing, the All-Seeing and All-Encompassing, while the latter is prescribed by man. Allah knows what the best is for man. Actually, man is prone to be influenced by many factors, i.e. common law, customs and environment and these factors are changeable. This is why the law prescribed by man that might suit a certain case could not suit another.